Ionizing Radiation Effects on Hs 578Bst Microtubules - Bruni, L.; Manghi, M.; Gioscio, E.; Caorsi, V.; Rizzi, F. M.; Croci, S. (Frontiers in Physics, 2020)
Microtubules are one of the three components of the cell cytoskeleton. They are hollow wires, with a diameter of about 25 nm, formed by 13 laterally associated protofilaments composed by dimers of - and β-tubulin. Microtubules are dynamic structures which constantly undergo constant modifications by shrinking and elongating in a phenomenon called treadmilling. Microtubules intervene in various fundamental aspects of the cell's biology. They contribute to determine the shape of a cell, play a role in the cell movement and in the intracellular transport of organelles during motion and mitotic chromo-some segregation. Despite the relevance of the processes mediated by microtubules most studies on the effects of ionizing radiations (IR) focus their attention on the damages delivered to DNA. In this paper we attempt to assess the effects borne by IRs to the microtubules network as a biological target. In this study we irradiated Hs 578Bst cells (a no-cancer, no-immortalized, human breast epithelial cell line) with a 8Gy single dose of either X-rays or protons. After the irradiated cells fixation the microtubules were imaged by means of Stochastic Optical Reconstruction Microscopy (STORM) to characterize the network disruption. In our results MT fibers integrity appears to not have been significantly affected at the administered dose of protons and X-rays, nonetheless we observed differences in the MT network distribution and fiber curvatures